LEXICAL AND ANALYTIC FRAMEWORK FOR CROSS-CULTURAL PHILOSOPHY STUDENTS - Mamatkulova Bakhtijon Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the integration of lexical and analytic frameworks in teaching philosophy to cross-cultural students. The lexical-analytic methodology emphasizes the relationship between language, cognition, and philosophical reasoning in multilingual contexts. It focuses on how lexical structures and analytic reasoning can be applied to enhance comprehension of philosophical texts in English. The study argues that the combined use of linguistic analysis and philosophical interpretation allows international students to develop deeper conceptual understanding and more effective communication skills. This interdisciplinary framework strengthens academic writing, critical thinking, and the appreciation of linguistic diversity within philosophical discourse.